2017
DOI: 10.18632/oncotarget.20827
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of androgen receptor expression in renal cell carcinomas

Abstract: BackgroundDespite rapid discoveries in molecular biology of renal cell carcinoma (RCC) and advances in systemic targeted therapies, development of new diagnostic and therapeutic strategies is urgently needed. The androgen receptor (AR) has been shown to hold prognostic and predicitve value in several malignancies. Here, we studied a possible association between AR expression and prognosis in patients with RCCs.ResultsLow AR expression levels were associated with occurrence of distant metastasis and higher tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…Zhu et al, 11 incontestable that AR expression rate was negatively accompanied pT stage and Fuhrman's grade in RCC patients. Also, this relationship was indicated by Foersch et al, 14 and Langner et al 9 , Zhu et al, 11 reported prevalence of AR had a negative relationship with pT stage and grade in RCC patients. Foersch et al, 14 and Langner et al, 9 reported the results opposite of him.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Zhu et al, 11 incontestable that AR expression rate was negatively accompanied pT stage and Fuhrman's grade in RCC patients. Also, this relationship was indicated by Foersch et al, 14 and Langner et al 9 , Zhu et al, 11 reported prevalence of AR had a negative relationship with pT stage and grade in RCC patients. Foersch et al, 14 and Langner et al, 9 reported the results opposite of him.…”
Section: Discussionmentioning
confidence: 72%
“…Also, this relationship was indicated by Foersch et al, 14 and Langner et al 9 , Zhu et al, 11 reported prevalence of AR had a negative relationship with pT stage and grade in RCC patients. Foersch et al, 14 and Langner et al, 9 reported the results opposite of him. Noh et al, 10 said AR expression related with the histological nuclear grade (p<0.027) and TNM stage (p<0.002).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The presence of AR in malignant melanoma cells supports metastatic potential and affects the development of distant metastases (8). On the other hand, the presence of AR in cells of clear cell or papillary kidney cancer seems to be associated with better clinical course and prognosis of the disease (9).…”
Section: The Role Of Androgen Receptors In Human Malignant Tumorsmentioning
confidence: 99%